Logotype as a part of brand visual identity - Strode, Aina; Stikute, Inga (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Aim of the article – to analyse the nature of corporate style and the development of logo, to take a qualitative research (case studies), evaluating specificities of the universities’ logo design in Latvia. This article studies and explains interrelated concepts of logo and corporate style. The analysis of Latvian universities logo shows the original unity of logo and national emblem which moving away over time. Logos of Latvian universities are characterized by a combination of symbols and fonts, visible in both location and the specialization and symbols of knowledge and growth. The logo design indicates trend towards minimalism that is successful, recognizable brand feature.